Atresia and Deformity of Nostrail in Cutaneous Tuberculosis - Masood H. Khan; Yogesh Bavishi; A. H. Khan (Indian Journal of Plastic Surgery)
A case of nasal atresia and deformity caused by tuberculosis in a 10 years old girl is presented.